System for Measuring Speed of Induction Motor - Petrovas, A.; Lisauskas, S.; Rinkevicienė, R. (Elektronika ir Elektrotechnika, 2010)
The article presents description of elaborated equipment for measurement of induction motor speed and current transients. Experimental results of motor current and speed at motor starting without load are measured and compared with simulated that. Results of comparison are used to determine adequacy of the induction motor model. It is stated, that model of induction motor, elaborated according to calculated coefficients, based on the rated parameters of the motor, is not enough adequate in the beginning of transients, where motor currents and speed are simulated with great errors.